Teachers’ and Students’ Needs in Scientific Work Skills: Guided Investigation Laboratory Module for Junior High Schools - Muin, Dewi; Ismet, Ismet; Marlina, Leni (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
Science practicum has an important role in fostering students’ scientific skills, but its implementation at the junior high school level still faces various obstacles, such as limited laboratory equipment and practicum guidelines that are not optimal. This study aims to analyze the needs of teachers and students for the implementation of science practicum as a basis for developing guided inquiry-based guidelines. The research method used was descriptive qualitative with data collection techniques through surveys and in-depth interviews. The research subjects consisted of 219 students and 52 junior high school science teachers in the South Sumatra region. The results of the analysis showed that 98.6% of students and 98,1% of teachers stated the importance of practicum guides, while only 34.4% of students and 40% of teachers had used or made inquiry-based guides. The majority of respondents supported the use of the guided inquiry approach because it is believed to be able to improve science process skills. However, limited tools and teacher understanding are the main obstacles to implementation. Therefore, the results of this study emphasize the need to develop guided inquiry-based science practicum guides that are systematic, applicable, and relevant to the context of junior high school learning.